Rembau District and Land Office / Noraini Ali - Ali, Noraini (Faculty of Business and Management, 2023)
contents, and acknowledgment, and followed by part two, which includes my updated resume. It also covers the company's profile, which is the company's background detailing the Rembau District and Land Office, the location of the office, the vision, mission, and objectives to achieve the company's goals, the charter, organisation chart, and product or services. In addition, training's reflection which is duration and time while I worked, details include of my department, roles, responsibilities, gains that I received which is allowance, knowledge and technical skills related to working, knowledge and gains new experience about new work environment. Besides, I also explain about several tasks and responsibilities during my industrial training at Rembau District and Land Office. In addition, the SWOT analysis explains three points of each of the criteria, which is for strength I choose work practice based on standard rules or regulation harmonies with current situation to explain and among the recommendations is an appreciation ceremony to give recognition to the staff and refreshment program to fix staffs mistake. For instance, the weakness, I choose workers are practicing ways of working and technologies that are way behind and lack of budgeting in terms of operation expenditure to explain it in detail and the recommendation is using Google Drive methods to secure staffs work and improving the budget. For opportunities, I choose Rembau is strategic place to develop to explain the recommendation that I suggest is upgrading plantation and tourism spot in Rembau to give opportunities to new generation, also increasing waqf land to give benefit's to others. For threat, I choose risk of being hacked and data loss to explain it and the recommendation is installing fire sprinkler system in office building and make two-authentication security on every platform of Email, Facebook, etc. In conclusion, I end my report with conclude the point regarding my internship for 6-months.